Palladium-catalyzed lignin valorization : Towards a lignin-based biorefinery - Galkin, Maxim (Uppsala universitet, Syntetisk organisk kemi, 2015)
The work described in this thesis focuses on the cleavage of the β-O-4′ bond, which is the most abundant interunit linkage in the lignin polymer. In the first part, three methods based on palladium catalysis have been developed and their applicability has been verified using lignin model compounds. A transfer hydrogenolysis of the β-O-4′ bond using formic acid as a mild hydrogen donor together with a base. An aerobic oxidation of the benzylic alcohol motif in the β-O-4′ linkage to generate a key intermediate in the cleavage reaction was performed. A redox neutral cleavage of the β-O-4′ bond was accomplished in which no stoichiometric reducing or oxidizing agents were added. In the second part of the thesis, a mechanistic study is presented. The corresponding ketone from a dehydrogenation reaction of the benzylic alcohol motif was identified to be the key intermediate. This ketone and its enol tautomer was found to be responsible for the β-O-4′ bond cleavage reaction under the employed reaction conditions. In the final part of this thesis, the methodologies have been applied to native lignin. The depolymerization reaction was combined with organosolv pulping. This approach was successful, and together with cellulose and hemicellulose, propenyl aryls were generated in excellent yields directly from wood. In this transformation, the lignin derived molecules have been reduced by an endogenous hydrogen donor from the wood.